(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes the works of modern German literature with intercultural potential. These are works that belong to “Intercultural Literature”: Sachbücher, Migrantenliteratur (works by migrant authors living in Germany, as well as works by German authors who have a long-term experience in excellent cultural contexts) and Frauenliteratur. Attention is drawn to the fact that the language and cultural landscape of Germany has essentially changed due to migration, mobility, globalization and integration processes. It affected the structure of society, turning them from monocultural to multicultural. Literature, which reflects the life of society in all its manifestations, now contains a powerful intercultural component, which is an essential social feature of the German present. In a multicultural environment, citizens need a “common language” for understanding. The emergence of such a “language” is possible only in terms of familiarity with “other” cultures, cultures of neighbors, their understanding and acceptance. Therefore, in recent decades in German literature there has been a large number of works that are known in the theory as “intercultural literature”. The texts of modern German literature, not only “intercultural”, have an extremely large intercultural potential, because they: reflect realities of everyday life of modern Germans in all variety of life situations; offer the reader actual problems that are close to different people from different cultural centers; recreate social relations and relationships between people; demonstrate examples of social behavior and thinking of modern Germans; their language is alive and figurative. This literature not only reflects the present-day Germany through the image of everyday life of ordinary citizens in a multicultural society, but also contains a comparative component of several cultures, with a focus on differences based on religious grounds, offering behavior patterns, communication styles, and t differences of time and space perceptions. It is not only a good material for the analysis of purely intercultural elements, but also a wealth of material for linguistic analysis.